Exposure to Bisphenol A increases malignancy risk of thyroid nodules in overweight/obese patients. (1st January 2023) - Marotta, Vincenzo; Grumetto, Lucia; Neri, Ilaria; Russo, Giacomo; Tortora, Anna; Izzo, Giulia; Panariello, Ilaria; Rocco, Domenico; Pezzullo, Luciano; Vitale, Mario
Abstract: Bisphenol A (BPA) is a widespread thyroid disruptor, but evidence about an association with thyroid cancer is weak. Excess body weight is a risk factor for thyroid cancer and affects activity of endocrine disruptors. Aim of the study was to investigate the association between BPA exposure and thyroid cancer, verifying the effect modification related to body weight. We performed a multicentre, cross-sectional study including consecutive patients referring for nodular goiter. The quantitative determination of BPA in serum samples was performed through high performance liquid chromatography system, coupled in tandem with ultraviolet and fluorescence detection. Ninety-six patients were included: 55 benign nodules, 41 thyroid cancers, 28 normal weight, and 68 overweight/obese. BPA was detected in 79 subjects. In the overall study population and in the group with BMI<25 kg/m 2 BPA exposure was not significantly correlated to thyroid cancer (p = 0.08 and 0.759, respectively). In the group with BMI≥25 kg/m 2, BPA-exposed subjects showed significantly higher risk of malignancy (OR: 5.3, p = 0.028). At multivariate analysis, such association was independent of smoking, alcohol consumption, occupational exposure, and phthalates exposure (p = 0.021 and 0.016, respectively), but was lost after adjustment for the presence of metabolic syndrome (p = 0.089). In overweight/obese subjects, BPA exposure was significantly associated with higher thyroid stimulating hormone levels. Our study suggests that BPA exposure is a risk factor for thyroid cancer in overweight/obese subjects. Graphical abstract: Image 1 Highlights: In overweight/obesity, BPA exposure increases malignancy risk of thyroid nodules. Overweight/obese patients exposed to BPA have higher TSH. Relationship between BPA and thyroid cancer is dependent on metabolic syndrome.